Antioxidant properties of some common oyster mushrooms grown in North East India - ANANTA SAIKIA, AFROZ MANSURI, DILIP KUMAR SARMAH* and (Indian Phytopathology, 2017)
Six oyster mushrooms, viz., Pleurotus ostreatus (Jacq. ex Fr.) P. Kumm., P. solidus (Schulz.) Sacc., P. djamor (Rumph.) Boedijn, P. florida (Mont.) Singer, P. sajor-caju (Fr.) Singer and P. citrinopileatus Singer were evaluated for their antioxidant properties. The antioxidant activity was more in pink coloured species (the highest in P. djamor, followed by P. ostreatus, and grey mushroom P. sajor-caju) than the white species (P. florida, P. sapidus and P. citrinopileatus), which established the positive effect of fruiting body pigmentation on antioxidant properties. A strong correlation between phenolic content and antioxidant activity was observed for all the species investigated. P. citrinopileatus showed higher chelating and radical scavenging effects than P. florida though it contained lower amount of phenol than P. florida. The investigation revealed the antioxidative potential of the pigmented mushrooms, viz., P. djamor and P. ostreatus. These species, enriched with beneficial bioactive components, have much potential for inclusion in breeding programmes and should be popularized for cultivation purpose.